EVALUATION OF WASTEWATER TREATMENT IN NUSA DUA TOURISM AREA AND THEIR CHALLENGES TO ALGAE BLOOM - Darwin, Darwin; Prajati, Gita; Adicita, Yosef; Suryawan, I Wayan Koko; Sarwono, Ariyanti (ASTONJADRO, 2021)
The wastewater treatment plant (WWTP) in the Nusa Dua area has implemented a stabilization pond to reduce organic matter and nutrients. Because it has been operating since 1980, it is necessary to evaluate the existing conditions. The aim of this study was to determine the percentage of organic and nutrient reduction from the WWTP system. Organic removal in the form of BOD and COD parameters were 71.84% and 75.11%, respectively. Meanwhile, nutrient parameters in the form of NH3-N, TN, and TP have a percentage of 83.64%; 59.41%, and -375.81%, respectively. TP is the only parameter that has increased, causing a problem which is caused by the explosion of algae population in the reservoir. TP allowance should be a concern in choosing advanced treatment.